Retinopathy of Prematurity –Recent Screening Status in a Tertiary Care Hospital of Bangladesh: Pharmaceutical Science-Pediatrics for Better Child Health - Dr. Maksudur Rahman; Dr. Dipak Kumar Nag; Md. Mahbubul Hoque; Dr. Liton Chandra Saha (International Journal of Life Science and Pharma Research, 2022)
Retinopathy of prematurity (ROP) results in severe visual impairment and blindness in newborns. In the recent days with development of the technology to save preterm infants, it’s incidence is increasing in both developed and developing countries. Only appropriate and timely screening program can prevent ROP and reduce the functional impairment of eyes. The aim of this study was to see the recent screening status of the hospital so that future plan of ROP treatment and prevention can be taken more appropriately. This prospective study was conducted from January 2018 to December 2018 in neonatology department of Dhaka Shishu (Children) Hospital. Neonates with gestational age < 34wks or birth weight, <1800gms were screened for ROP. First screening was done at 4 wks chronological age or 32 wks postmenstrual age of neonate which comes later. Then subsequent screening was done according to the findings upto 45 wks of postmenstrual age. The findings regarding incidence of ROP, types of ROP and treatment modalities of ROP along with other variables were recorded. Data were analyzed with SPSS version 17. Total 116 cases were screened for ROP. Mean gestational age was 30.7±2.4 wks and mean weight was 1420.9±313.8 gms. According to gestational age, 14 (12%) neonates with gestational age < 28 wks had ROP. Nine (7.8%) cases had ROP in both gestational age groups of 29-30wks and 31-32wks. Only 5(4.3%) cases with gestational age 33-34wks had ROP. According to birth weight, neonates with birth weight <1000 gms had ROP in 1(0.9%). Twenty four (20.7%) and 12(10.3%) cases had ROP in weight groups of 1000-1499gms and 1500-1800 gms consequently. Thirty one (26.8%) cases were found ROP in their first visit. In 6(5.1%) cases ROP were found in 2nd and subsequent visits. Among the neonates, A-P ROP was present in 15(12.9%) cases, type -1 in 9 (7.7%), type- 2 in 11 (9.6%) and RD in 2(1.7%) cases. Three (2.6%) cases of type 2 ROP turned into type- 1 ROP in subsequent visits. Among the ROP cases, total 29(78%) needed treatment. Laser therapy was given in 7(24%) cases, both laser and intravitreal bivacizumab in 17 (59%) cases, only intravitreal bivacizumab in 2(7%) cases and surgery along with medical treatment was advised for 3(10%) cases. Thirty four (92%) cases had good outcome and 3 (8%) infant had no vision.The incidence of ROP was 31.9% in this study. Most of cases were A-P ROP then Z2S3 ROP. Laser plus intravitreal bivacizumab were given in most of the cases with ROP. The more number of advanced stages of ROP and a large number of babies required treatment indicates that these babies came to us in advanced stages due to irregularity and missing of follow-up.